National Resilience Based on Family Resilience during the Covid-19 Pandemic in Bandung Regency - Rofi’ Ramadhona Iyoega; Rike Anggun Artisa; Cintantya Andhita Dara Kirana (Institut Pendidikan Indonesia, 2021)
National resilience will only be realized when it is supported by resilience in the layers below, namely regional/regional resilience. Regional/regional resilience is also impossible to create if there is no resilience at the family (self/individual) level. The Covid-19 pandemic has the potential to threaten the national resilience of the Indonesian nation. Therefore, the role of the family as a supporting pillar of national resilience must be increased. The family as the smallest social unit in society has the responsibility to produce the next generation who is superior and competitive, educating the nation's children who have balanced intellectual, moral and spiritual intelligence. This article aims to explain the condition of family resilience during the Covid-19 Pandemic and explain the contribution of families in realizing community resilience which has an impact on strengthening the nation's national resilience. Data collection in this research was carried out using the interview method and distributing questionnaires to respondents. A qualitative approach was chosen in this study through a study of relevant literature.